Semiotics and linguistics: for an interpretation of cultural change - Sonia Liced Sánchez Rivera (Corporación Universitaria Minuto de Dios, 2008)
This article establishes a relationship between some of the theoretical assumptions of semiotics and linguistics, in order to explain the transformations of contemporary culture whose practices and verbal signs as fathomed today transcend compromising other modes of communication. This new attempt by the culture demands alternative approaches that generate less description and more interpretation, because, as shown in the text, culture phenomena of meaning holds that shape its history and gear make social action, practical action and signs that are revealed from discursive consciousness that emerges from a semiotic concept of culture.